INTERVENSI KEBENCANAAN MELALUI KELEMBAGAAN LOKAL: Pengalaman Dari Desa Wilayah Pesisir Lampung - Ikram Ikram; Usman Raidar; Anita Damayantie; Zikri Zikri (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2023)
This paper describes interventions in disaster management through the role of local institutions. The focus of the intervention is on the knowledge and skills capacity of coastal villagers in disaster management. The analysis is conducted on the role of the local disaster institution Siaga Bencana Berbasis Masyarakat (SIBAT) initiated by the Indonesian Red Cross (PMI) and the Regional Disaster Management Agency (BPBD) of South Lampung District. Qualitative research methods were used to explore the role of SIBAT and the parties in the effort to increase disaster knowledge and disaster preparedness skills and sensitivities. Data collected through in-depth interviews and observations. Interviews involved 14 informants with the main criteria as disaster social activists. Case study conducted in Way Muli Timur Village, Rajabasa District, South Lampung Regency. The forms of capacity building activities identified are natural disaster socialization, training in natural disaster prevention and natural disaster risk reduction, natural area vulnerability mapping, natural disaster management training, organizational and network development, preparation of Standard Operating Procedures (SOPs), and disaster simulations. The results showed that increasing the capacity of community knowledge and skills in preventing and coping with disasters can be done through the participatory village assessment method.